Наступність реалізації ігрових форм у роботі з дошкільниками в умовах ЗДО - Устимчук, Суламіта Олександрівна (My University, 2023)
Магістерська робота виконана на теоретичному та емпіричному рівнях. На теоретичному рівні, внаслідок аналізу існуючих психолого-педагогічних досліджень, обґрунтований категоріально-понятійний апарат з проблеми організації освітньої діяльності дітей дошкільного віку в умовах ЗДО. Проаналізована роль ігрових форм у роботі з дошкільниками. Визначили та обґрунтували педагогічні умови забезпечення наступності ігрових форм у роботі з дітьми дошкільного віку в умовах закладу освіти. На емпіричному рівні, в межах педагогічного експерименту, нами було вивчено стан забезпеченості наступності ігрових форм у роботі з дошкільниками в умовах закладу дошкільної освіти. Розроблена рекомендована система роботи з оптимізації педагогічних умов забезпечення наступності в реалізації ігрових форм взаємодії з дітьми у ЗДО.
The master's thesis was performed at theoretical and empirical levels. At the theoretical level, as a result of the analysis of existing psychological and pedagogical research, the categorical and conceptual apparatus on the problem of organizing the educational activities of preschool children in the conditions of preschool educational institutions is substantiated. The role of game forms in work with preschoolers is analyzed. The pedagogical conditions for ensuring the continuity of game forms in the work with preschool children in the conditions of an educational institution are determined and substantiated. At the empirical level, within the framework of the pedagogical experiment, we studied the state of ensuring the continuity of game forms in the work with preschoolers in the conditions of preschool education. The recommended system of work on optimization of pedagogical conditions for ensuring continuity in the implementation of game forms of interaction with children in preschool educational institutions has been developed. Key words: educational activity, continuity, game forms, preschool children, continuity of game forms in work with preschool children
Keywords: освітня діяльність; наступність; ігрові форми; діти дошкільного віку; наступність ігрових форм у роботі з дошкільниками; гра